Tollip is a mediator of protein sumoylation. - Alessia Ciarrocchi; Romina D'Angelo; Chiara Cordiglieri; Ada Rispoli; Spartaco Santi; Massimo Riccio; Simona Carone; Anna Laura Mancia; Simone Paci; Elena Cipollini; Davide Ambrosetti; Marialuisa Melli (PLoS ONE)
Tollip is an interactor of the interleukin-1 receptor involved in its activation. The endosomal turnover of ubiquitylated IL-1RI is also controlled by Tollip. Furthermore, together with Tom1, Tollip has a general role in endosomal protein traffic. This work shows that Tollip is involved in the sumoylation process. Using the yeast two-hybrid technique, we have isolated new Tollip partners including two sumoylation enzymes, SUMO-1 and the transcriptional repressor Daxx. The interactions were confirmed by GST-pull down experiments and immunoprecipitation of the co-expressed recombinants. More specifically, we show that the TIR domain of the cytoplasmic region of IL-1RI is a sumoylation target of Tollip. The sumoylated and unsumoylated RanGAP-1 protein also interacts with Tollip, suggesting a possible role in RanGAP-1 modification and nuclear-cytoplasmic protein translocation. In fact, Tollip is found in the nuclear bodies of SAOS-2/IL-1RI cells where it colocalizes with SUMO-1 and the Daxx repressor. We conclude that Tollip is involved in the control of both nuclear and cytoplasmic protein traffic, through two different and often contrasting processes: ubiquitylation and sumoylation.